2021
DOI: 10.1038/s43246-021-00153-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral surfaces and coatings and their mechanisms of action

Abstract: Viral infections are a serious health challenge, and the COVID-19 pandemic has increased the demand for antiviral measures and treatments for clean surfaces, especially in public places. Here, we review a range of natural and synthetic surface materials and coatings with antiviral properties, including metals, polymers and biopolymers, graphene and antimicrobial peptides, and their underpinning antiviral mechanisms. We also discuss the physico-chemical properties of surfaces which influence virus attachment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
179
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 216 publications
3
179
0
2
Order By: Relevance
“…For example, copper species may inactivate metalloenzymes by replacing native metal ions. 32 Another mechanism is that Cu 2 O is thought to produce ROSs, including superoxide (O 2 –• ), hydroxyl radicals (•OH), and hydrogen peroxide (H 2 O 2 ), which can oxidize biological materials. 35 Typically, this oxidation begins with superoxide and/or hydrogen peroxide, which are produced by bacteria but not viruses.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, copper species may inactivate metalloenzymes by replacing native metal ions. 32 Another mechanism is that Cu 2 O is thought to produce ROSs, including superoxide (O 2 –• ), hydroxyl radicals (•OH), and hydrogen peroxide (H 2 O 2 ), which can oxidize biological materials. 35 Typically, this oxidation begins with superoxide and/or hydrogen peroxide, which are produced by bacteria but not viruses.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some coatings have been developed to meet this objective, both for SARS-CoV-2 25 29 and bacteria, 30 , 31 and have been reviewed recently. 32 34 In addition, considerable research has investigated the antimicrobial properties of metals and metal oxides, 35 41 textured antimicrobial surfaces, 42 44 and antimicrobial additives to face masks. 45 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nanomaterials possess virucidal potential and provide novel routes for the development of antiviral systems utilizing the dual functionality of NPs. Antiviral nanosystems can be applied as antiviral barriers to coat frequently contacted surfaces, such as masks, public areas, and healthcare infrastructure [183]. The use of antiviral nanomaterials, including copper [184], graphene oxide [168], zinc oxide [185], and AgNPs [186], has Survival rates, clinical scores, and body weights of (i) mice without infection and mice injected with (ii) PBS, (iii) curcumin, or (iv) Cur-CQDs, followed by challenge with EV71.…”
Section: Viral Inhibitionmentioning
confidence: 99%
“…Cu coatings, i.e., virucidal properties of copper alloy and copper surfaces, have been tested in several studies. It was proven that a small percentage of copper had a significant effect on virucidal properties [7]. In another study on copper alloys, rapid inactivation of human coronavirus 229E was observed, and Cu/Zn brasses were very effective at lower copper concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition rate depends upon the size of particles in electrode material, workpiece material, and experimental conditions. This work focuses on coating copper alloy on a workpiece as it has various applications in wastewater treatment plants as antiviral coatings in this COVID pandemic times [7]. Since virucidal coating has to have Cu/Zn, bronze, an alloy of copper, was considered electrode material in this study.…”
Section: Introductionmentioning
confidence: 99%